2009
DOI: 10.1902/jop.2009.080545
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Smoking With Superoxide Dismutase Enzyme Levels in Subjects With Chronic Periodontitis

Abstract: There was a progressive reduction in SOD levels from healthy non-smokers to light smokers to heavy smokers. These findings highlight the need to augment the efforts of smoking-cessation programs. The benefits of reduced smoking and improved antioxidant levels may motivate smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 26 publications
8
66
4
1
Order By: Relevance
“…In the present study, lower GPx activity in chronic periodontitis group is observed than in controls. Similar findings were reported by studies [26,32]. Guentsch et al [36] have showed that periodontally healthy subjects demonstrated significantly lower levels of GP x than the periodontitis group including smokers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, lower GPx activity in chronic periodontitis group is observed than in controls. Similar findings were reported by studies [26,32]. Guentsch et al [36] have showed that periodontally healthy subjects demonstrated significantly lower levels of GP x than the periodontitis group including smokers.…”
Section: Discussionsupporting
confidence: 82%
“…Smoking is associated with altered expression and activity of antioxidant enzymes. According to the studies [32,33] cigarette smoking is associated with a significant decrease in the level of SOD, however some other studies [34,35] have documented that compared to non smoker controls the bidi smokers have shown increased erythrocyte SOD activity. We have observed a relatively higher SOD Values are mean ± SD * P values are obtained using one way analysis of variance (ANOVA) with Tukey's correction for multiple group comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…While Panjamurthy et al (52) reported significantly higher SOD levels in periodontitis compared to controls, Akalın et al (54,55) reported lower SOD in periodontitis patients. In our study, the decreases in SOD levels in rats affected by periodontitis were not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the association between periodontitis severity and antioxidant enzyme levels have yielded inconsistent results (51)(52)(53). While Panjamurthy et al (52) reported significantly higher SOD levels in periodontitis compared to controls, Akalın et al (54,55) reported lower SOD in periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by Agnihotri's study, which compared average levels of superoxide dismutase (SOD) in the GCF and saliva of smokers and non-smokers with periodontitis, there was a significant reduction in superoxide dismutase levels in smokers compared to non-smoker subjects. Moreover, it was proved that there was a gradual decrease in the levels of SOD of the GCF and saliva from light smoking to heavy smoking (11).…”
Section: Introductionmentioning
confidence: 98%